Effect of Flipped Classroom Model on Indonesian EFL Students’ Writing Achievement across Cognitive Styles - Mubarok, Ahsin Fahmi; Cahyono, Bambang Yudi; Astuti, Utari Praba (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
Recently, there have been a lot of studies examining the effect of the application of flipped classroom model. However, most of the studies focused on students’ achievement without much regard on cognitive styles. This study was aimed to investigate the effect of flipped classroom model on Indonesian EFL students’ writing achievement across cognitive styles (i.e., field dependent and field independent). It involved 58 university students from two intact classes which were divided into experimental and control groups. Both groups were given a pre-test and a post-test to know their writing achievement before and after treatment. The results of the study revealed that the mean score of the students from the experimental group was significantly higher than that of the students from the control group (p < 0.016). This study also uncovered the significantly different interaction of students from each cognitive style.